2005
DOI: 10.1111/j.1444-2906.2005.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on thermal denaturation modes of myosin in walleye pollack and carp myofibrils as affected by salt concentration

Abstract: The effect of salt concentration on the thermal denaturation profile of myosin in walleye pollack and carp myofibrils was compared by studying the subfragment-1 (S-1) and rod denaturation rates upon heating. Species-specific denaturation mode observed at 0.1 M KCl was no longer detected when samples were heated above 0.5 M KCl, where S-1 and rod denaturation rates were identical to each other. As the heating of the chymotryptic digest of myofibril formed practically no rod aggregates, S-1 denaturation in a for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…Ca 2+ -ATPase inactivation was well explained by the decrease of amount of S-1 reasonably because ATPase active site locates in the part, which was the same conclusion as obtained with fish myofibrils [9]. Loss of salt solubility and monomeric myosin content was well explained by the rod denaturation.…”
Section: Changes Insupporting
confidence: 72%
See 3 more Smart Citations
“…Ca 2+ -ATPase inactivation was well explained by the decrease of amount of S-1 reasonably because ATPase active site locates in the part, which was the same conclusion as obtained with fish myofibrils [9]. Loss of salt solubility and monomeric myosin content was well explained by the rod denaturation.…”
Section: Changes Insupporting
confidence: 72%
“…1 A fast rod denaturation relative to S-1 was characteristic for scallop myofibrils heated at 0.1 M KCl. We reported that relatively large magnitude of stabilization by F-actin leads to a fast rod denaturation with fish species [9]. A rapid denaturation of rod observed with scallop myofibrils can be explained similarly with a great stabilization extent.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The magnitude calculated with catfish was about 100 times, which was the same as tilapia and was much greater than those calculated with carp and Alaska pollock myofibrils showing only 10 to 30 times [18].…”
mentioning
confidence: 86%